Trauma Exposure and Intimate Partner Violence Among Young Pregnant Women in Liberia - Sileo, Katelyn M. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a global threat to women’s health and may be elevated among those exposed to traumatic events in post-conflict settings, such as Liberia. The purpose of this study was to examine potential mediators between lifetime exposure to traumatic events (i.e., war-related trauma, community violence) with recent experiences of IPV among 183 young, pregnant women in Monrovia, Liberia. Hypothesized mediators included mental health (depression, posttraumatic stress symptoms), insecure attachment style (anxious and avoidant attachment), and attitudes indicative of norms of violence (attitudes justifying wife beating). We tested a parallel multiple mediation model using the PROCESS method with bias-corrected and accelerated bootstrapping to test confidence intervals (CI). Results show that 45% of the sample had experienced any physical, sexual, or emotional IPV in their lifetime, and 32% in the 2 months prior to the interview. Exposure to traumatic events was positively associated with recent IPV severity (β = .40, p < .01). Taken together, depression, anxious attachment style, and justification of wife beating significantly mediated the relationship between exposure to traumatic events and experience of IPV (β = .15, 95% CI = [0.03, 0.31]). Only anxious attachment style (β = .07, 95% CI = [0.03, 0.16]) and justification of wife beating (β = .05, 95% CI = [0.01, 0.16]) were identified as individual mediators. This study reinforces pregnancy as an important window for both violence and mental health screening and intervention for young Liberian women. Furthermore, it adds to our theoretical understanding of mechanisms in which long-term exposure to traumatic events may lead to elevated rates of IPV in Liberia, and points to the need for trauma-informed counseling and multilevel gender transformative public health approaches to address violence against women.